Smart home security - Mohammad Syafi Azim, Mohd Razam (2019)
Home bursts are growing in Malaysia. Every year home-breaking cases are increasingly being heard in social media and television. Most home-based cases occur due to several factors. One of the key system weaknesses. Most users in Malaysia use lock keys for the lock. The mango lock has the advantage of being simple keys and unique keys of each mango but it has its disadvantages that are easy to crack and easy to create extra keys. Mango keys are easily broken by pirates as they may learn from YouTube. Therefore, to address this problem, this project proposes a system that allows users to lock the door easily and safely. The objective of building this system is to lock the door of the house using android or voice app and to control the door of the house using a mobile phone that helps the user to see the door of the house anytime and anywhere. Rapid Application Development is the method used to develop this application. The RAD methodology consists of four main stages, the first is the planning stage of the need, the design stage, the stages of construction, and the last is the stallion level. After the application has been developed, customers will be given a user acceptance test (UAT) to ensure that all functions are in accordance with the requirements without any mistake. The UAT test will ensure that the application meets all objectives and can be used to solve current problems regarding home security. Based on system testing, users lock the door easily by using the Home Intelligence System. It hopes that the proposed system will benefit the interested parties.